Keberagaman Semu dan Dilema Minoritas di Kota Banda Aceh - Fasya, Teuku Kemal (Faculty of Islam Nusantara, Nahdlatul Ulama University of Indonesia (Unusia) Jakarta., 2021)
This study examines the understanding of the concept of diversity (pluralism and multiculturalism) in the city of Banda Aceh; the capital city of Aceh Province which is now more than 800 years old. Can the city be classified as a diversity-friendly city as it is embedded for Pematang Siantar, Manado, Kupang, or Bali, which are among the most diversity friendly regions and are tolerant to other religions and beliefs? This study adopts socio-qualitative with an ethnographic approach to present arguments about the diversity in the city of Banda Aceh. The analytical instrument seeks to empathize with Banda Aceh's value of inductivity, as well as its